2006
DOI: 10.1093/geronb/61.4.p237
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Validation of a Model of Reminiscence and Health in Later Life

Abstract: This study addresses the adaptive value of functions of reminiscence with respect to physical and mental health in later life. A model examining the relationships between the functions of reminiscence and life satisfaction, psychiatric distress, and health is presented and tested. Self-positive (reminiscence for Identity, Death Preparation, and Problem Solving) and self-negative (reminiscence for Boredom Reduction, Bitterness Revival, and Intimacy Maintenance) functions have statistically significant and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
138
1
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(163 citation statements)
references
References 38 publications
(58 reference statements)
12
138
1
8
Order By: Relevance
“…autobiographical retrieval practice) with (depressed) older adults, have shown unequivocally that having or developing a positive/meaningful view of the past is linked with well-being and mental health in terms of higher life satisfaction, decreased depressive and anxiety symptoms, less feelings of hopelessness, and positive or negative emotions (Cappeliez, O'Rourke & Chaudhury, 2005;Cappeliez, Guindon & Robitaille, 2008;Fry, 1983;Pot, Bohlmeijer, Onrust, Melenhorst, Veerbeek & De Vries, 2010;Serrano, Latorre, Gatz & Montanes, 2004;. Obsessive and escapist reminiscences (akin to Past-Negative TP) are associated with psychological distress such as depression and anxiety (Cully, LaVoie & Gfeller, 2001) and lower satisfaction with life (Cappeliez & O'Rourke, 2006).…”
Section: Time Perspective Linked To Subjective Well-being In Later Lifementioning
confidence: 99%
“…autobiographical retrieval practice) with (depressed) older adults, have shown unequivocally that having or developing a positive/meaningful view of the past is linked with well-being and mental health in terms of higher life satisfaction, decreased depressive and anxiety symptoms, less feelings of hopelessness, and positive or negative emotions (Cappeliez, O'Rourke & Chaudhury, 2005;Cappeliez, Guindon & Robitaille, 2008;Fry, 1983;Pot, Bohlmeijer, Onrust, Melenhorst, Veerbeek & De Vries, 2010;Serrano, Latorre, Gatz & Montanes, 2004;. Obsessive and escapist reminiscences (akin to Past-Negative TP) are associated with psychological distress such as depression and anxiety (Cully, LaVoie & Gfeller, 2001) and lower satisfaction with life (Cappeliez & O'Rourke, 2006).…”
Section: Time Perspective Linked To Subjective Well-being In Later Lifementioning
confidence: 99%
“…Life stories and SWB may promote each other by solidifying a positive and meaningful outlook on one's self and life in ways that compensate for age-related losses (Birren and Schroots 2006;Bluck and Habermas 2001). However, life stories and SWB may also impair each other by reviving negative, and possibly traumatic, experiences that induce a further sense of vulnerability in later life (Cappeliez and O'Rourke 2006;Wong and Watt 1991). This study addresses the conundrum of how the perceived past relates to present SWB.…”
Section: Introductionmentioning
confidence: 99%
“…The positive ability (to recall good things, be prepared for death, and be able to solve problems) and negative ability (to reminisce about sad and profound events) are both significantly associated with psychological well-being among the elderly (Cappeliez and O'Rourke, 2006). From evidence-based studies of reminiscence used to improve psychological wellbeing, using the Affect Balance Scale (ABS), Short Form 36 General Health Survey (SF-36), and the General Questionnaire (GHQ) it was found that reminiscence helped people to improve psychological well-being, with the average ABS score increasing from 1.5-10.9 to 3.2-14.9 ( p < .05) (Fielden, 1990;Haight and Dias, 1992;Haight et al, 1998;Haight et al, 2000;Tatchell and Jordan, 2004).…”
Section: Introductionmentioning
confidence: 99%